SOSIALISASI PENGGUNAAN SISTEM PENGOLAHAN DATA TABUNGAN NASABAH BERBASIS WEBSITE PADA BANK SAMPAH SAKURA - Rika Sadariawati; Malahayati; Ebtaria Nadeak; Ina Opi Aprina; Ulam Muhammad Rapy; Meranda (Politeknik Negeri Sriwijaya, 2024)
To maximize data processing, the role of technology is very important, including in recording customer savings data at Bank Sampah Sakura. Sakura Waste Bank, especially the management, records customer savings data every day. So far, the process of processing customer savings data at Bank Sampah Sakura is still recorded manually and simply, so that there is socialization of the implementation of a website-based customer financial data processing system to Sakura Waste Bank partners. The stage of this activity is to conduct workshops to see partners' needs and then carry out socialization and evaluation of activities. From the results of the evaluation carried out on partners, it is known that partners' understanding in processing customer savings data after socialization is 82% .